Konsep Perlindungan Hukum Pekerja Migran Indonesia di Luar Negeri - Budiantoro, Totok; Yulianis, M. Sifa Fauzi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Indonesia is the country that sends the largest number of Indonesian workers abroad and is able to generate the second largest foreign exchange after the oil and gas sector of more than 159 trillion rupiah. It is very clear that Indonesian workers have contributed a lot to the country. The country's high foreign exchange earnings from migrant workers abroad also have many problems. To deal with these problems, the government established a non-ministerial institution which is tasked with and responsible for placement and protection services. Overseas Indonesian workers are the Indonesian Migrant Worker Protection Agency (BP2MI). The aim of this research is to determine the role of the Indonesian government through BP2MI in providing protection for Indonesian workers, where the state has an obligation to protect every citizen, without exception and to find out the condition of PMIs. The method used in this research is a qualitative method, and data collection techniques include literature study and interviews. So, the author can describe how the BP2MI program is implemented in protecting PMI abroad. In implementing the placement and protection of PMI, BP2MI cannot work alone, but by collaborating and coordinating with other institutions or agencies that are involved with the placement and protection of Indonesian migrant workers abroad.